Classification of non-Hodgkin lymphoma in Algeria according to the World Health Organization classification. Issue 4 (April 2015) - Boudjerra, Nadia; Perry, Anamarija M.; Audouin, Josée; Diebold, Jacques; Nathwani, Bharat N.; MacLennan, Kenneth A.; Müller-Hermelink, Hans K.; Bast, Martin; Boilesen, Eugene; Armitage, James O.; Weisenburger, Dennis D.
Abstract The relative distribution of non-Hodgkin lymphoma (NHL) subtypes differs markedly around the world. The aim of this study was to report this distribution in Algeria. A panel of four hematopathologists classified 197 consecutive cases according to the World Health Organization classification, including 87.3% B-cell and 12.7% T- or natural killer (NK)-cell NHLs. This series was compared with similar cohorts from Western Europe (WEU) and North America (NA). Algeria had a significantly higher frequency of diffuse large B-cell lymphoma (DLBCL: 52.8%) and a lower frequency of follicular lymphoma (FL: 13.2%) compared with WEU (DLBCL: 32.2%; FL: 20.0%) and NA (DLBCL: 29.3%; FL: 33.6%). The frequency of mantle cell lymphoma was lower in Algeria (2.5%) compared with WEU (8.3%). Smaller differences were also found among the NK/T-cell lymphomas. In conclusion, we found important differences between Algeria and Western countries, and further epidemiologic studies are needed to explain these differences.